Intra-unionist disputes in Northern Ireland house of commons, 1921-72 - Whyte, JH (Economic & Social Studies, 1973)
This is a report on a research project carried out in 1972, and again in 1973, by students taking the special subject in the Government of Ireland, in the Political Science Department at the Queen's University of Belfast. The object was to ascertain, from the division lists printed in the Northern Ireland Hansard, to what extent and on what issues Unionist back-benchers were likely to vote against the government.
Keywords: Politics; Northern Ireland